Mark Manders : Coloured room with black and white scene. (Arnhem : ROMA, 1999)
Book with isolated titels. Only one titel has been worked out into a series of 12 color photographs showing a complex installation : A coloured room with a black and white scene.
Engels
boek
Keywords: Manders, Mark